Apriori Algorithm Implementation on Market Basket Analysis (MBA) of Mobile Phone Accessories - Erwin Dwika Putra; Muhammad Husni Rifqo; Depmi Hardianto (Jurnal Komputer, Informasi dan Teknologi, 2022)
Theuse of data mining techniques presently help business owners to facilitate the promotion of their product marketing. One of the most techniques is well-known as association analysis. This association analysis aims to find the relationship between the goods purchased by customers. This kind of association analysis is commonly known as market basket analysis. Market basket analysis uses customer data that has been stored in the database to find new information in it. The apriori algorithm, is applied an algorithm for conducting market basket analysis, which aims to find the most frequently purchased items. This apriori algorithm produces an association rule that is useful for business actors. By analyzing the association a priori algorithm can be seen that customers’ data can be used as input for business owners to determine sales strategies for their business.